Microfluidic encapsulation for controlled release and its potential for nanofertilisers. (13th September 2021) - Le, Tu Nguyen Quang; Tran, Nam Nghiep; Escribà-Gelonch, Marc; Serra, Christophe A.; Fisk, Ian; McClements, David Julian; Hessel, Volker
Abstract : Nanotechnology is increasingly being utilized to create advanced materials with improved or new functional attributes. Abstract : Nanotechnology is increasingly being utilized to create advanced materials with improved or new functional attributes. Converting fertilizers into a nanoparticle-form has been shown to improve their efficacy but the current procedures used to fabricate nanofertilisers often have poor reproducibility and flexibility. Microfluidic systems, on the other hand, have advantages over traditional nanoparticle fabrication methods in terms of energy and materials consumption, versatility, and controllability. The increased controllability can result in the formation of nanoparticles with precise and complex morphologies ( e.g., tuneable sizes, low polydispersity, and multi-core structures). As a result, their functional performance can be tailored to specific applications. This paper reviews the principles, formation, and applications of nano-enabled delivery systems fabricated using microfluidic approaches for the encapsulation, protection, and release of fertilizers. Controlled release can be achieved using two main routes: (i) nutrients adsorbed on nanosupports and (ii) nutrients encapsulated inside nanostructures. We aim to highlight the opportunities for preparing a new generation of highly versatile nanofertilisers using microfluidic systems. We will explore several main characteristics of microfluidically prepared nanofertilisers, including droplet formation, shell fine-tuning, adsorbate fine-tuning, and sustained/triggered release behavior.